An efficient color LED driver based on self-configuration current mirror circuit - Durrani, Shaheer Shaida; Abu Zaharin, Ahmad; Bakri, Hassan; Khan, Atif Sardar; Nawaz, Asif; Jan, Naveed; Ali Khan, Rehan; Tariq, Rohi; Shah, Ahmed Ali; Bashir, Tariq; Khan, Zia Ullah; Ahmed, Sheeraz (The Science and Information (SAI) Organization Limited, 2021)
The string channel of Color LED driver with precise current balancing is proposed. It is noted that to drive a multiple LEDs string is by using a proper current source, due to the level of the brightness LED depends on the quantity of the current flows. In the production of LEDs, the variation in the forward voltage for each LED has been found significantly high. This variation causes different levels of brightness in LEDs. Then, controlling load current of LED by using a resistor to limit the LED current flowing is considered by associated with the forward voltage, instantly. Current sources have been designed to become immune to the above problem since it regulates the current, and not the voltage which flows through the LEDs. Hence, constant current source is the essential requirement to drive the LEDs. Besides, it is complex for color LEDs, dependent on the number of control nodes and dimming configuration. To arrange an accurate load current for the different sets of string color LEDs, the efficient LED driver is required, in which the current sharing is complement to each LED strings. Therefore, this paper suggests a color LED driver with self-configuration of enhanced current mirrors in multiple LED strings. The load currents have been efficiently balanced among the identical loads and unequal loads. The comparable efficiency of the string color LEDs losses has been shown thoroughly.